Seeds to succeed: Sequential giving to public projects - Anat Bracha; Michael Menietti; Lise Vesterlund (Federal Reserve Bank of Boston, 2009)
The public phase of a capital campaign is typically launched with the announcement of a large seed donation. Andreoni (1998) argues that such a fundraising strategy may be particularly effective when funds are being raised for projects that have fixed production costs. The reason is that the introduction of fixed costs may give rise to both positive and zero provision outcomes, and absent announcements of a large seed gift, donors may get stuck in an equilibrium that fails to provide a desirable public project. Interestingly, Andreoni (1998) demonstrates that announcing seed money can help eliminate such inferior outcomes. We investigate this model experimentally to determine whether announcements of seed money eliminate the inefficiencies that may result under fixed costs and simultaneous provision. To assess the strength of the theory we examine the effect of announcements in both the presence and absence of fixed costs. Our findings are supportive of the theory for projects with sufficiently high fixed costs.
Keywords: 330; Spendensammlung; Theorie